Straw-based biodegradable composite material as well as preparation method and application thereof

Through the combination of straw fiber, modified polylactic acid and quaternary ammonium antibacterial agent, a straw-based biodegradable composite material with excellent mechanical properties and antibacterial properties was prepared, which solved the long degradation cycle and antibacterial properties of traditional disposable tableware. The problem of insufficient is suitable for disposable tableware, meeting the market's demand for mechanical strength and antibacteriality.

CN119119700AInactive Publication Date: 2024-12-13WENZHOU XINBANG ENVIRONMENTAL PROTECTION TECH CO LTD

Patent Information

Application Number
CN202411615701.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional petroleum-based disposable tableware has a long degradation cycle and insufficient antibacterial performance, making it difficult to meet the mechanical strength and antibacterial requirements in the field of disposable tableware. In addition, pure straw fiber composite materials have shortcomings in water resistance and mechanical properties.

Method used

Using straw fiber, modified polylactic acid and prepared quaternary ammonium antibacterial agents as raw materials, melt extrusion and granulation and hot pressing are used to prepare a straw-based biodegradable composite material, combined with glycerol and sodium alginate to enhance the mechanical properties and antibacterial properties of the material.

Benefits of technology

It achieves excellent mechanical properties and antibacterial properties of disposable tableware, and has good biodegradability, extends service life, reduces health risks caused by bacterial pollution, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119700A_ABST
    Figure CN119119700A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biodegradable food packaging materials, and particularly relates to a straw-based biodegradable composite material as well as a preparation method and application thereof. The straw-based biodegradable composite material is prepared from the following components in parts by weight: 10 to 20 parts of straw fiber, 65 to 80 parts of modified polylactic acid, 2 to 5 parts of bacteriostatic agent, 0.5 to 1.5 parts of glycerol and 1 to 3 parts of sodium alginate. The bacteriostatic agent is prepared through a series of chemical reactions and has a novel structure. The straw-based biodegradable composite material prepared by the invention is green and environment-friendly tableware which has excellent antibacterial activity, high mechanical strength and good water resistance and is biodegradable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biodegradable food packaging materials, and specifically relates to a straw-based biodegradable composite material and a preparation method and application thereof. Background Art

[0002] Disposable tableware plays an indispensable role in our current life. Its widespread use has greatly facilitated people's lives, but it has also brought serious environmental pollution problems. Traditional petroleum-based disposable tableware has a long degradation cycle, which has had a serious impact on natural ecology and biodiversity. Therefore, the scientific research community is actively seeking environmentally friendly alternatives. Polylactic acid (PLA) has become an important candidate material to replace traditional disposable tableware due to its environmental friendliness and easy biodegradability (decomposed into carbon dioxide and water through the natural cleavage of the main chain ester bond) from renewable plant resources. However, in practical applications, especially in areas with frequent consumption such as disposable tableware, PLA materials are limited in their widespread application due to their high hardness and insufficient toughness, as well as their lack of sufficient antibacterial properties.

[0003] In order to enhance the antibacterial properties of PLA, the existing technology has tried to use a variety of antibacterial agents, including zinc oxide (patent CN108752884A), modified lignin and modified chitosan (patent CN111286178A), etc. Zinc oxide has attracted attention for its broad-spectrum antibacterial properties and relative safety, but its dispersibility and long-term stability in PLA still need to be optimized; modified lignin and modified chitosan use the biocompatibility and degradability of natural polymers to improve the antibacterial effect through chemical modification, but their antibacterial strength and environmental adaptability still have room for improvement.

[0004] As a transformation product of crop waste (such as corn straw, rice straw, wheat straw, etc.), straw fiber has a rich resource base and potential environmental value. Converting straw into biodegradable disposable tableware can not only realize the resource utilization of agricultural waste and reduce the pressure of environmental treatment, but also promote the development of circular economy. However, pure straw fiber composite materials have obvious deficiencies in mechanical properties and water resistance, and it is difficult to directly meet the diversified needs of the market, especially in the field of disposable tableware, which has high requirements for the antibacterial properties and mechanical strength of the materials to ensure food safety and prevent foodborne diseases caused by microbial contamination.

[0005] Based on the above background, the present invention prepares a straw-based biodegradable composite material with both antibacterial and high mechanical strength for the preparation of disposable tableware, which not only provides a new idea and method for improving the antibacterial performance of PLA materials, but also opens up a new way for the resource utilization of agricultural waste such as straw, which is of great significance for promoting the widespread application of green and environmentally friendly materials and the sustainable development of environmental protection. Summary of the invention

[0006] The first purpose of the present invention is to provide a straw-based biodegradable composite material, which is made by using natural straw as a matrix and then compounding it with modified polylactic acid, an antibacterial agent, etc. It is a green and environmentally friendly material with excellent mechanical properties, good water resistance, and biodegradability.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is: A straw-based biodegradable composite material, comprising the following components in parts by weight: 10-20 parts of straw fiber, 65-80 parts of modified polylactic acid, 2-5 parts of antibacterial agent, 0.5-1.5 parts of glycerol, and 1-3 parts of sodium alginate; The preparation of the antibacterial agent comprises the following steps: (1) Mixing o-aminobiphenyl, potassium nitrate and sulfuric acid and reacting them. After the reaction is completed, pouring the reaction solution into water, and post-treating the reaction solution to obtain intermediate 1; (2) adding intermediate 1 and 2-chloro-4-fluoro-5-nitrotrichlorotoluene to a solvent, adding tin tetrachloride to react, and after the reaction is completed, post-treating the reaction solution to obtain intermediate 2; (3) adding intermediate 2 to ethanol and then adding a catalyst to react under a hydrogen atmosphere. After the reaction is completed, the reaction liquid is post-treated to obtain intermediate 3; (4) The intermediate 3 and glycidyl trimethylammonium chloride are added to an acetic acid solution for reaction. After the reaction is completed, the reaction solution is post-treated to obtain the antibacterial agent.

[0008] Furthermore, in step (1), the dosage ratio of o-aminobiphenyl, potassium nitrate and sulfuric acid is 10 mmol: (50-70 mmol): (20-30 mL), the reaction temperature is -5-0°C, and the reaction time is 4-6 h.

[0009] Furthermore, in step (2), the solvent is nitrobenzene, the molar ratio of the intermediate 1, 2-chloro-4-fluoro-5-nitrotrichlorotoluene and tin tetrachloride is 1:(1.5-2):(0.05-0.12), the reaction temperature is 170-180°C, and the reaction time is 20-24h.

[0010] Furthermore, in step (3), the catalyst is Pd / C, and the mass ratio of the intermediate 2 to the catalyst is 1:(0.1-0.15).

[0011] Furthermore, in step (4), the molar ratio of the intermediate 3 to glycidyl trimethylammonium chloride is 1:(10-12), the reaction temperature is 50-60° C., and the reaction time is 4-6 h.

[0012] Furthermore, the preparation of the modified polylactic acid comprises the following steps: The lactic acid monomer is mixed with a catalyst, a polyacid or a hydroxy acid under vacuum conditions, heated, and subjected to copolymerization to obtain modified polylactic acid.

[0013] Furthermore, the lactic acid monomer is L-lactic acid.

[0014] Furthermore, the catalyst is stannous chloride, the polyacid is succinic acid, and the hydroxy acid is one of tartaric acid or hydroxyacetic acid.

[0015] Furthermore, the mass ratio of the polylactic acid, the catalyst, the polyacid or the hydroxy acid is 1: (0.001-0.003): (0.05-0.07), the temperature of the heating reaction is 200-220° C., and the reaction time is 2-4 hours.

[0016] The second object of the present invention is to provide a method for preparing a straw-based biodegradable composite material.

[0017] In order to achieve the above object, the technical solution adopted by the present invention is: The method for preparing the above-mentioned straw-based biodegradable composite material comprises the following steps: a weighed straw fiber, modified polylactic acid, antibacterial agent, glycerol, sodium alginate according to the above parts by weight, stirred and mixed, and dried to obtain a mixture; b. The mixture in step a was melt extruded and granulated by a twin-screw extruder to obtain pellets; c. Add the pellets of step b into the mold, hot press at 150 ℃ ~ 180 ℃, 5 ~ 10 MPa for 30-50min, and demold after molding; d. Dry and sterilize the demoulded sample to obtain the biodegradable composite material.

[0018] Furthermore, the straw fiber is one of corn straw fiber, soybean straw fiber and wheat straw fiber.

[0019] The third object of the present invention is to provide applications of straw-based biodegradable composite materials.

[0020] In order to achieve the above object, the technical solution adopted by the present invention is: Such as the application of the straw-based biodegradable composite material in the preparation of disposable tableware.

[0021] Compared with the prior art, the beneficial technical effects of the present invention are: 1. The present invention uses straw fiber, modified polylactic acid and prepared antibacterial agent as raw materials to obtain a straw-based biodegradable composite material, which can be used to prepare disposable tableware. The disposable tableware has excellent mechanical properties and antibacterial properties, as well as good biodegradability, and is a completely biodegradable green and environmentally friendly tableware.

[0022] 2. The present invention combines the characteristics of quaternary ammonium salt antibacterial agent, i.e., its broad-spectrum bactericidal property, low toxicity and good stability, and designs and prepares a novel quaternary ammonium salt molecular antibacterial agent. The antibacterial agent can overcome the problems of uneven dispersion of traditional quaternary ammonium salts in PLA and poor compatibility with matrix materials through fine molecular structure design, and not only gives the composite material antibacterial property, but also does not affect the mechanical properties of PLA. In addition, the present invention also prepares modified polylactic acid by copolymerizing lactic acid monomer with polyacid or hydroxy acid, and through modification of polylactic acid and its proportioning with straw fiber, the disposable tableware prepared has excellent mechanical properties.

[0023] 3. The straw-based biodegradable composite material prepared by the present invention can be used to prepare disposable tableware. Through antibacterial modification treatment, the service life of the disposable tableware is extended, and the health risks caused by bacterial contamination are reduced. It has broad application prospects in industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The antibacterial rate results of the products obtained from Examples 1 to 3 of the present invention and Comparative Examples 1 to 2 are shown in FIG. DETAILED DESCRIPTION

[0025] Below, the present invention is further described in conjunction with specific embodiments. It should be noted that, under the premise of no conflict, the embodiments described below or the technical features can be arbitrarily combined to form new embodiments. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.

[0026] Example 1 A straw-based biodegradable composite material, comprising the following components in parts by weight: 15 parts of corn straw fiber, 75 parts of modified polylactic acid, 3.5 parts of antibacterial agent, 1 part of glycerol, and 2 parts of sodium alginate; The preparation process of the antibacterial agent is as follows:

[0027] (1) Add o-aminobiphenyl (10 mmol) to 20 mL of 98% concentrated sulfuric acid, then add potassium nitrate (60 mmol), maintain the reaction temperature at 0°C, and react for 5 h. After the reaction is completed, pour the reaction solution into water under stirring to terminate the reaction. Concentrate the resulting reaction solution, and then purify it by column to obtain intermediate 1. (2) Intermediate 1 (10 mmol) and 2-chloro-4-fluoro-5-nitrotrichlorotoluene (17 mmol) were added to 50 mL of nitrobenzene, and tin tetrachloride (1 mmol) was added as a catalyst. The reaction was carried out at 175°C for 22 h. After the reaction was completed, the reaction solution was poured into water to remove the unreacted 2-chloro-4-fluoro-5-nitrotrichlorotoluene, leaving the oil phase. The oil phase was crystallized at 20°C for 16 h, and then the crystalline precipitate was filtered and washed with methanol. After drying, intermediate 2 was obtained. (3) Add intermediate 2 (1 g) to 200 mL of ethanol and reflux, add 0.13 g of 10% Pd / C, and stir at room temperature under normal pressure and hydrogen atmosphere for 2.5 h. After the reaction is completed, filter and then concentrate the filtrate in vacuo to obtain intermediate 3; The above intermediate 3 1 HNMR (C 19 H 14 CIF 4 , 400MHz, DMSO- d6 )δ: 8.38(d, 1H), 7.84(d,1H), 7.60-7.59(m,2H), 7.23-7.15(m, 3H), 6.96(s, 1H), 5.34-5.30(d,4H),4.64(s,2H); mass spectrometry analysisMS (ESI + ): [M+H] + Calculated to be 353.09, found to be 353.09; the above results confirmed that the obtained product was the target product.

[0028] (4) The intermediate 3 (10 mmol) was added to 100 mL of 2% acetic acid solution, and then glycidyl trimethylammonium chloride (110 mmol) was added thereto. The reaction was carried out at 55 °C for 5 h. After the reaction was stopped, the reaction solution was concentrated and purified by column to obtain the product, i.e., the antibacterial agent.

[0029] The above antibacterial agents 1 HNMR (C 37 H 56 Cl 4 FN 7 O 3 , 400MHz, DMSO- d6 )δ: 9.53(s, 2H), 8.99(s, 1H), 8.36(d, 1H), 7.87(d, 1H), 7.58-7.57(m, 2H), 7.21-6.94(m, 4H),5.37(s,3H), 4.17(m, 3H),3.50-3.06(m,39H); Mass spectrometry analysisMS (ESI +): [M+H] + Calculated to be 806.32, found to be 806.32; the above results confirmed that the obtained product was the target product.

[0030] The preparation of modified polylactic acid comprises the following steps: 100 g of L-lactic acid was mixed with 0.1 g of stannous chloride and 5 g of tartaric acid under vacuum conditions, heated to 210° C., and copolymerized for 3 h. The product after the copolymerization reaction was taken out from the high-temperature reactor and cooled to room temperature. The copolymer was dissolved in dichloromethane. The copolymer solution was added to ethanol as a precipitant under stirring conditions to precipitate the polymer, thereby separating it from other impurities. The treated copolymer was dried to remove residual solvent and moisture, thereby obtaining modified polylactic acid. The method for preparing the above-mentioned straw-based biodegradable composite material comprises the following steps: a. The corn straw fiber was crushed through a 100 mesh sieve and dried for 2h; according to the above parts by weight, corn straw fiber, modified polylactic acid, antibacterial agent, glycerol, sodium alginate were weighed, stirred and mixed, and dried to obtain a mixture; b. The mixture in step a was melt extruded and granulated by a twin-screw extruder to obtain pellets; c. Add the pellets of step b into the mold, set the hot pressing temperature to 160 ° C, the hot pressing pressure to 7.5 MPa, the hot pressing time to 40min, and demold after molding; d. Dry and sterilize the demoulded sample to obtain the biodegradable composite material.

[0031] Example 2 A straw-based biodegradable composite material comprises the following components in parts by weight: 10 parts of corn straw fibers, 65 parts of modified polylactic acid, 2 parts of antibacterial agent, 0.5 parts of glycerol and 1 part of sodium alginate.

[0032] The preparation process of the antibacterial agent is as follows: (1) Add o-aminobiphenyl (10 mmol) to 25 mL of 98% concentrated sulfuric acid, then add potassium nitrate (50 mmol), maintain the reaction temperature at -5 °C, and react for 6 h. After the reaction is completed, pour the reaction solution into water under stirring to terminate the reaction. Concentrate the resulting reaction solution, and then purify it by column to obtain intermediate 1; (2) Intermediate 1 (10 mmol) and 2-chloro-4-fluoro-5-nitrotrichlorotoluene (15 mmol) were added to 50 mL of nitrobenzene, and tin tetrachloride (0.5 mmol) was added as a catalyst. The reaction was carried out at 170 °C for 24 h. After the reaction was completed, the reaction solution was poured into water to remove the unreacted 2-chloro-4-fluoro-5-nitrotrichlorotoluene, leaving the oil phase. The oil phase was crystallized at 20 °C for 16 h, and then the crystalline precipitate was filtered and washed with methanol. After drying, intermediate 2 was obtained. (3) Add intermediate 2 (1 g) to 200 mL of ethanol and reflux, add 0.1 g of 10% Pd / C, and stir at room temperature under normal pressure and hydrogen atmosphere for 2 h. After the reaction is completed, filter and then concentrate the filtrate in vacuo to obtain intermediate 3; (4) The intermediate 3 (10 mmol) was added to 100 mL of 2% acetic acid solution, and then glycidyl trimethylammonium chloride (100 mmol) was added thereto. The reaction was carried out at 50 °C for 6 h. After stopping the reaction, the reaction solution was concentrated and purified by column to obtain the product, i.e., the antibacterial agent.

[0033] The preparation of modified polylactic acid comprises the following steps: 100 g of L-lactic acid was mixed with 0.2 g of stannous chloride and 6 g of glycolic acid under vacuum conditions, heated to 200° C., and copolymerized for 4 hours. The product after the copolymerization reaction was taken out from the high-temperature reactor and cooled to room temperature. The copolymer was dissolved in dichloromethane. The copolymer solution was added to ethanol as a precipitant under stirring conditions to precipitate the polymer, thereby separating it from other impurities. The treated copolymer was dried to remove residual solvent and moisture, thereby obtaining modified polylactic acid. The method for preparing the above-mentioned straw-based biodegradable composite material comprises the following steps: a. Same as step a in Example 1; b. The mixture of step a is melt extruded and granulated by a twin-screw extruder to obtain pellets; c. Add the pellets of step b into the mold, set the hot pressing temperature to 150 ° C, the hot pressing pressure to 5 MPa, the hot pressing time to 50min, and demold after molding; d. Dry and sterilize the demoulded sample to obtain the biodegradable composite material.

[0034] Example 3 A straw-based biodegradable composite material comprises the following components in parts by weight: 20 parts of corn straw fiber, 80 parts of modified polylactic acid, 5 parts of antibacterial agent, 1.5 parts of glycerol and 3 parts of sodium alginate.

[0035] The preparation process of the antibacterial agent is as follows: (1) Add o-aminobiphenyl (10 mmol) to 30 mL of 98% concentrated sulfuric acid, then add potassium nitrate (70 mmol), maintain the reaction temperature at 0°C, and react for 4 h. After the reaction is completed, pour the reaction solution into water under stirring to terminate the reaction. Concentrate the resulting reaction solution, and then purify it through a column to obtain intermediate 1. (2) Intermediate 1 (10 mmol) and 2-chloro-4-fluoro-5-nitrotrichlorotoluene (20 mmol) were added to nitrobenzene, and tin tetrachloride (1.2 mmol) was added as a catalyst. The reaction was carried out at 180°C for 24 h. After the reaction was completed, the reaction solution was poured into water to remove the unreacted 2-chloro-4-fluoro-5-nitrotrichlorotoluene, leaving the oil phase. The oil phase was crystallized at 20°C for 16 h, and then the crystalline precipitate was filtered and washed with methanol. After drying, intermediate 2 was obtained. (3) Add intermediate 2 (1 g) to 200 mL of ethanol and reflux, add 0.15 g of 10% Pd / C, and stir at room temperature under normal pressure and hydrogen atmosphere for 3 h. After the reaction is completed, filter and then concentrate the filtrate in vacuo to obtain intermediate 3; (4) Intermediate 3 (10 mmol) was added to 100 mL of 2% acetic acid solution, and then glycidyl trimethylammonium chloride (120 mmol) was added thereto. The reaction was carried out at 60 °C for 4 h. After the reaction was stopped, the reaction solution was concentrated and purified by column to obtain the product, i.e., the antibacterial agent.

[0036] The preparation of modified polylactic acid comprises the following steps: 100 g of L-lactic acid was mixed with 0.3 g of stannous chloride and 7 g of succinic acid under vacuum conditions, heated to 220° C., and copolymerized for 2 h. The product after the copolymerization reaction was taken out from the high-temperature reactor and cooled to room temperature. The copolymer was dissolved in dichloromethane. The copolymer solution was added to ethanol as a precipitant under stirring conditions to precipitate the polymer, thereby separating it from other impurities. The treated copolymer was dried to remove residual solvent and moisture, thereby obtaining modified polylactic acid. The method for preparing the above-mentioned straw-based biodegradable composite material comprises the following steps: a. The same as step a in Example 1; b. The mixture in step a was melt extruded and granulated by a twin-screw extruder to obtain pellets; c. The pellets of step b are added to the mold, and the hot pressing temperature is set to 160 ° C, the hot pressing pressure is 10 MPa, the hot pressing time is 30min, and the mold is released after molding; d. Dry and sterilize the demoulded sample to obtain the biodegradable composite material.

[0037] Comparative Example 1 This comparative example provides a straw-based biodegradable composite material and a preparation method thereof, which is different from Example 1 in that polylactic acid is used instead of modified polylactic acid, and the rest is consistent with Example 1.

[0038] Comparative Example 2 This comparative example provides a straw-based biodegradable composite material and a preparation method thereof, which is different from Example 1 in that the antibacterial agent is replaced with chitosan quaternary ammonium salt, and the rest is consistent with Example 1.

[0039] Comparative Example 3 This comparative example provides a straw-based biodegradable composite material and a preparation method thereof, which is different from Example 1 in that the antibacterial agent is omitted, and the rest is consistent with Example 1.

[0040] Test Example 1 The mechanical properties were tested according to the experimental standard of GB / T1040.1-2018 "Determination of tensile properties of plastics", as follows: the samples to be tested in Examples 1 to 3 and Comparative Examples 1 to 3 were prepared into the size of dumbbell type II, placed in an environment of 25°C and a relative humidity of 50%, and the tensile strength and elongation at break of the materials were tested using a material tensile testing machine. The tensile rate was set to 50 mm / min, and 5 parallel experiments were performed on each group of samples, and the average value was taken as the final experimental result, as shown in Table 1.

[0041] Table 1 Mechanical properties test results Group Tensile strength (MPa) Elongation at break (%) Example 1 36.15 515 Example 2 34.47 502 Example 3 35.69 510 Comparative Example 1 25.12 368 Comparative Example 2 29.56 435 Comparative Example 3 35.18 519 It can be seen from the experimental results of Table 1 that compared with Comparative Example 1 using polylactic acid, Examples 1-3 use modified polylactic acid instead of polylactic acid, and the tensile strength and elongation at break of the material are significantly improved. This is because the modified polylactic acid can be inserted into the molecular chain of the straw fiber, which is easier to form a supporting structure, and there is an intermolecular interaction force between the straw fiber, thereby improving the tensile strength of the composite material. Comparative Examples 2 and 3 are compared with Example 1. It can be seen that due to the poor compatibility of the common chitosan quaternary ammonium salt with the modified polylactic acid and the straw fiber in Comparative Example 2, the tensile strength and elongation at break of the material are worse than those of Example 1 and Comparative Example 3. The mechanical properties of the materials obtained in Comparative Example 3 and Example 1 are not much different, which also shows that the antibacterial agent prepared by the present invention has good compatibility with the modified polylactic acid and the straw fiber, and will not affect the mechanical properties of the material.

[0042] Based on the above experimental results, it can be seen that the biodegradable composite material of the present invention has good mechanical properties, can meet the requirements of disposable tableware on mechanical properties, and can be used in industrial production.

[0043] Test Example 2 Antibacterial test: The samples prepared in Examples 1-3 and Comparative Examples 1-2 were cut into a circle with a diameter of 6 mm and sterilized by ultraviolet for 5 h. Escherichia coli and Staphylococcus aureus were selected as experimental strains. 100 μL of Escherichia coli suspension (10 6 CFU / mL and Staphylococcus aureus suspension (10 6 CFU / mL) was evenly applied to the corresponding culture medium surface with a sterile applicator, and the cut circular sample was pressed against the center of the culture dish with sterilized tweezers. Then it was inverted and cultured in a 37°C incubator for 24 hours. The diameter of the inhibition zone was observed. The average value of three parallel experiments in each group was taken as the final test result, as shown in Table 2.

[0044] Antibacterial rate: The antibacterial rate of the product obtained by the present invention was determined by the shaking bottle method. 0.2 g of the products of Examples 1 to 3 and Comparative Examples 1 to 3 were weighed and sterilized by ultraviolet irradiation for 5 h. The Example 1 to 3 group and the Comparative Example 1 to 2 group were respectively set as the experimental group. After cutting into pieces, 5 mL of Escherichia coli suspension (10 6 CFU / mL and Staphylococcus aureus suspension (10 6 CFU / mL), the mixed solution was placed in a constant temperature shaker at 37°C and 200rpm, and the shaking culture was continued for 12 hours. Then, the absorbance value of each group at 600nm was tested using an ELISA instrument, and the average value was taken as the final experimental data. The absorbance value measured here indicates that the reproduction of microorganisms is inhibited when the product prepared by the present invention exists. At the same time, a blank control group needs to be set up, that is, the bacterial solution without adding the sample, and the absorbance test is also performed. The antibacterial rate of each group of products is calculated according to the calculation formula of the antibacterial rate: Antibacterial rate (%) = (A 0 -A n ) / A 0 ×100%, where A n is the absorbance value of the bacterial solution in the experimental group, A 0 is the absorbance value of the bacterial solution in the blank control group. Figure 1 shown.

[0045] Table 2 Antibacterial test results

[0046] Table 2 is the antibacterial activity test results of the products obtained from Examples 1 to 3 of the present invention and Comparative Examples 1 to 2. Figure 1 The results of the antibacterial rate of the products obtained in Examples 1 to 3 of the present invention and Comparative Examples 1 to 2 are shown in FIG. From the above results, it can be seen that the products obtained in Examples 1 to 3 of the present invention all have excellent antibacterial properties against Escherichia coli and Staphylococcus aureus. Among them, the diameter of the antibacterial circle and the antibacterial rate of Comparative Example 2 are reduced. This experimental result shows that the antibacterial agent prepared in the present invention can effectively improve the antibacterial effect of the composite material.

[0047] Test Example 3 Degradability test: The samples to be tested in Examples 1 to 3 which were dried to constant weight were cut into 2 cm × 2 cm squares and buried in a rectangular tray filled with humus soil, wherein the soil was taken from a vegetable garden and the same amount of distilled water was sprayed every day to maintain the relative humidity of the soil. The weight of the sample was recorded before the start of the experiment, recorded as M1; the samples were taken out after 60 days and 120 days, respectively, and the soil on the surface of the sample was cleaned with clean water and ethanol, respectively, and dried to constant weight, recorded as M2; the calculation formula for the degradation rate is as follows: Degradation rate (%) = (M1-M2) / M1×100%, M1 represents the initial weight of the sample, and M2 represents the constant weight of the material measured at different times. The experimental results are shown in Table 3.

[0048] Table 3 Degradability test results Group 60-day degradation rate (%) 120-day degradation rate (%) Example 1 65.91 96.92 Example 2 64.63 95.44 Example 3 65.15 96.78 From the experimental results in Table 3, it can be seen that the degradation rate of the composite material described in Example 1 of the present invention reached 65.91% on the 60th day of the experiment. It can be almost completely biodegraded in 120 days, and the effects of Examples 2 and 3 are similar, indicating that the composite material obtained by the present invention has good complete biodegradability and helps to reduce the pressure of environmental pollution. This is because under the action of microorganisms and moisture in the soil, the molecular chain of the material is broken, causing the material to gradually degrade.

[0049] In summary, the products prepared in Examples 1 to 3 of the present invention have the best comprehensive performance, have relatively ideal antibacterial activity, and have high mechanical properties, and are suitable for use as disposable tableware.

[0050] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A straw-based biodegradable composite material, characterized in that: The invention comprises the following ingredients in parts by weight: 10-20 parts of straw fiber, 65-80 parts of modified polylactic acid, 2-5 parts of antibacterial agent, 0.5-1.5 parts of glycerol, and 1-3 parts of sodium alginate; The preparation of the antibacterial agent comprises the following steps: (1) Mixing o-aminobiphenyl, potassium nitrate and sulfuric acid and reacting them. After the reaction is completed, pouring the reaction solution into water, and post-treating the reaction solution to obtain intermediate 1; (2) adding intermediate 1 and 2-chloro-4-fluoro-5-nitrotrichlorotoluene to a solvent, adding tin tetrachloride to react, and after the reaction is completed, post-treating the reaction solution to obtain intermediate 2; (3) adding intermediate 2 to ethanol and then adding a catalyst to react under a hydrogen atmosphere. After the reaction is completed, the reaction liquid is post-treated to obtain intermediate 3; (4) The intermediate 3 and glycidyl trimethylammonium chloride are added to an acetic acid solution for reaction. After the reaction is completed, the reaction solution is post-treated to obtain the antibacterial agent.

2. The straw-based biodegradable composite material according to claim 1, characterized in that: In step (1), the molar ratio of o-aminobiphenyl to potassium nitrate is 1:(5-7), wherein the concentration of o-aminobiphenyl in sulfuric acid is 0.33-0.5 mol / L, the reaction temperature is -5-0°C, and the reaction time is 4-6 hours.

3. The straw-based biodegradable composite material according to claim 1, characterized in that: The solvent of step (2) is nitrobenzene, the molar ratio of the intermediate 1, 2-chloro-4-fluoro-5-nitrotrichlorotoluene and tin tetrachloride is 1:(1.5-2):(0.05-0.12), the reaction temperature is 170-180°C, and the reaction time is 20-24h.

4. The straw-based biodegradable composite material according to claim 1, characterized in that: The catalyst in step (3) is Pd / C, and the mass ratio of the intermediate 2 to the catalyst is 1:(0.1-0.15).

5. The straw-based biodegradable composite material according to claim 1, characterized in that: In step (4), the molar ratio of the intermediate 3 to glycidyl trimethylammonium chloride is 1:(10-12), the reaction temperature is 50-60° C., and the reaction time is 4-6 h.

6. The straw-based biodegradable composite material according to claim 1, characterized in that: The preparation of the modified polylactic acid comprises the following steps: The lactic acid monomer is mixed with a catalyst, a polyacid or a hydroxy acid under vacuum conditions, heated, and subjected to copolymerization to obtain modified polylactic acid.

7. The straw-based biodegradable composite material according to claim 1, characterized in that: The catalyst is stannous chloride, the polyacid is succinic acid, and the hydroxy acid is one of tartaric acid or hydroxyacetic acid.

8. The straw-based biodegradable composite material according to claim 1, characterized in that: The mass ratio of the polylactic acid, the catalyst, the polyacid or the hydroxy acid is 1: (0.001-0.003): (0.05-0.07), the temperature of the heating reaction is 200-220° C., and the reaction time is 2-4 hours.

9. The method for preparing the straw-based biodegradable composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: a weighed straw fiber, modified polylactic acid, antibacterial agent, glycerol, sodium alginate according to the above parts by weight, stirred and mixed, and dried to obtain a mixture; b. The mixture in step a was melt extruded and granulated by a twin-screw extruder to obtain pellets; c. Add the pellets of step b into the mold, hot press at 150 ℃ ~ 180 ℃, 5 ~ 10 MPa for 30-50min, and demold after molding; d. Dry and sterilize the demoulded sample to obtain the biodegradable composite material.

10. Use of the straw-based biodegradable composite material according to claim 9 in the preparation of disposable tableware.

Citation Information

Patent Citations

  • Composite material mixed with outdoor biodegradable poly-lactic acid and straws and preparation method of composite material

    CN109181254A

  • Application of amino fullerenes in preparing antibacterial materials and antibacterial material

    CN109223828A

  • Akt inhibitor intermediate SM1 and preparation method thereof

    CN109384708A

  • Synthesis method of (E)-3,5-dihydroxy-4-isopropyl stilbene

    CN112250546A

  • Modified straw / polylactic acid composite material and preparation method thereof

    CN114395229A

Cited By

  • Antibacterial food-grade plastic product for sealing and fresh keeping and preparation method of antibacterial food-grade plastic product

    CN122080473A